Combined and Distributional Effects of EPL Reduction and Hiring Incentives: An Assessment Using Non-Linear DiD - Chiara Ardito; Fabio Berton; Lia Pacelli (Institute of Labor Economics (IZA), 2019)
Two decades of unsuccessful marginal labour market reforms provided the political support to reduce the flexibility gap between temporary and open-ended workers by means of a retrenchment of the employment protection benefitting the latter. To support employment levels during the crisis years, these policies have generally been combined with generous employment subsidies. While the theoretical and empirical literature on the two interventions taken in isolation appears generally abundant, almost nothing is known when they come combined. Analogously, no evidence is available about their distributional effects. This paper aims at filling these two gaps by means of non-linear difference-in-differences duration models estimated on high-frequency employer-employee linked Italian data. Taking advantage of the quasi-experimental conditions set by the Italian "Jobs Act", we find that large firms are less sensitive than small ones to hiring subsidies, unless they come combined with lower firing costs. Small firms substitute temporary for permanent employment, while larger ones do not seem to give up on fixed-term contracts, possibly as a probationary period. The reforms have benefitted domestic workers over foreigners, and those with a lower or more general human capital. No gender effects emerge.
Keywords: J08; J63; 330; employment protection legislation; hiring incentives; non-linear DiD; duration models; impact evaluation; jobs act